2013
DOI: 10.1038/nature12577
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic chromosome structures constrain and respond to designation of crossover sites

Abstract: Crossover (CO) recombination events between homologous chromosomes are required to form chiasmata, temporary connections between homologs that ensure their proper segregation at meiosis I1. Despite this requirement for COs and an excess of the double-strand DNA breaks (DSBs) that are the initiating events for meiotic recombination, most organisms make very few COs per chromosome pair2. Moreover, COs tend to inhibit the formation of other COs nearby on the same chromosome pair, a poorly understood phenomenon kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
235
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(254 citation statements)
references
References 32 publications
17
235
2
Order By: Relevance
“…2). Turning and twisting morphologies of the SC have been observed before in many different organisms, and it has been hypothesized that the twisting may play a role in recombination through an asyet unclear mechanism (3,7,20,29). Although the turning morphologies that we observed do not appear to be regular or helical, it is possible that some of them contain levels of torsion that may be necessary for recombination.…”
Section: Resultscontrasting
confidence: 48%
“…2). Turning and twisting morphologies of the SC have been observed before in many different organisms, and it has been hypothesized that the twisting may play a role in recombination through an asyet unclear mechanism (3,7,20,29). Although the turning morphologies that we observed do not appear to be regular or helical, it is possible that some of them contain levels of torsion that may be necessary for recombination.…”
Section: Resultscontrasting
confidence: 48%
“…This overall pattern also fits with the fact that leptotene is characterized specifically by chromatin expansion, whereas zygotene is characterized specifically by chromosome compaction (20). Indeed, even in Caenorhabditis elegans, in which CO interference occurs after SC formation, recent findings indicate that the chromosomes are under chromatin expansion stress caused by the constraints of the SC, in accord with a role for expansion stress in CO designation (29). ii) In the context of this proposed model, it is easy to envision that, as the designation/interference process progresses, local precursor reactivity will be insufficient to give CO designation; however, if passage of the interference signal implies decreased chromatin expansion, SC nucleation will be progressively favored as the process progresses, thus permitting/ promoting a continued designation process that gives SC nucleations without accompanying CO designation, exactly as suggested by the current analysis.…”
Section: Complex Spatial Patterns Can Arise In a Single Interference-supporting
confidence: 58%
“…Recent work has demonstrated that the C. elegans SC central region proteins are important not only for promoting the formation of meiotic COs, but also for limiting their numbers by contributing to CO interference (Hayashi et al 2010;Libuda et al 2013). Inherent in the concept of CO interference is the ability of a nascent CO to change the environment in which it occurs in a manner that inhibits other recombination events in its vicinity from maturing into COs.…”
Section: Implications Of a Two-state View Of The Scmentioning
confidence: 99%